Electrochemical Studies of o- and p- Anisidine - Sharma, Richa; Dave, Sushma (International Journal of Applied Sciences and Biotechnology, 2015)
Electrochemical oxidation of methyl substituted aniline (anisidine) has been done on both gold and platinum electrode using cyclic voltammetry. The results were compared in different supporting electrolytes such as KCl, KNO3, H2SO4, HCl. Effect of pH was observed on electrochemical oxidation of o- & p- anisidine at gold and platinum electrode. During various scan single oxidation peak during first forward scan with no corresponding cathodic peak was obtained while a new anodic cathodic couple peak appears in subsequent scan obtained. Kinetic parameters like heterogeneous rate constant, transfer co-efficient and diffusion co-efficient were also calculated. A sensitive method was developed for estimation of micro quantities of anisidine by linear sweep voltammetry and hydrodynamic voltammetry.Int J Appl Sci Biotechnol, Vol 3(2): 267-271 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12615